Examining The Effect of Psychological Factors Towards Consumers’ Groceries Purchasing Decision at Aeon Serpong BSD - Alifia Yasmin (Administratif Profesional, 2022)
Studying core elements of marketing science and customer behaviour is a crucial feature that any businessman should have. Consumer behaviour is a process that is inextricably linked to the presence of a purchasing process. A businessman frequently has difficulties accurately understanding and assessing customer demands and behaviour owing to the numerous aspects that impact consumer behaviour, and each consumer has a different behavior. This study aims to examine the influence of psychological factors such as motivation, perception, personality, and attitude towards consumers’ groceries purchasing decision at Aeon BSD. The population in this study were Aeon BSD customers. The sampling technique used was convenience sampling and data collection methods through an online questionnaire to 260 respondents who fit the population criteria. Based on the results of this study indicate that attitude has the most significant effect on consumers’ purchasing decisions, followed by perception, and personality.